Analisis Kinerja Keuangan PT. Pertamina (Persero) Tahun 2020-2022: Financial Performance Analysis of PT. Pertamina for 2020-2022 - Alif firmansyah; M. Nakula anjani putra S; nailatur rohmah; Putri ayy nanda sholehah; alfina khotimatus sa diah; Risma susila; ithrotul farach (Universitas Bojonegoro, 2024)
PT Pertamina (Persero) is one of the largest state-owned enterprises in Indonesia engaged in energy and oil and gas. Financial ratio analysis is important to understand the company's financial performance. This study aims to analyze the financial performance of PT. Pertamina (Persero) during the 2020-2022 period using liquidity, solvency, profitability, activity, and market ratios. This research uses descriptive methods with quantitative and qualitative approaches. Data obtained from the consolidated financial statements of PT Pertamina (Persero) for 2020-2022. The analysis results show that PT Pertamina has high liquidity ratios, activity ratios, and profitability ratios, indicating good financial performance. However, the company's leverage ratio is also high, indicating a high level of debt. The market ratio decreased significantly in 2022. The financial performance of PT Pertamina (Persero) is generally good during the period 2020-2022. However, it should be noted that the high leverage ratio and declining market ratio in 2022 need management attention.